The French Huguenots - Norton, Virginia Viola (My University, 1904)
Introduction: In the early part of the sixteenth century we find that the established church, in many places had almost reached its lowest limit in spirituality. The priesthood in these places was corrupt to the last degree. All forms of dissipation and licentiousness were indulged in by the priests, the nobles and working classes, alike. In the north however a change was taking place, and it was finally forced upon the people by Martin Luther. He saw the folly of the church and lamented it, Luther did much for reforming the church but out of Switzerland came the man who was the father of the Huguenots. John Calvin, by his writing and his patient, untiring effort, brought…
Citation: Norton, Virginia Viola. The French Huguenots. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Huguenots; France; Sixteenth Century; European History; Theses; Manuscripts (documents)